Ferroptosis and the ubiquitin-proteasome system: exploring treatment targets in cancer - Din, Muhammad Azhar Ud; Lin, Yan; Wang, Naijian; Wang, Bo; Mao, Fei (Frontiers in Pharmacology, 2024)
Ferroptosis is an emerging mode of programmed cell death fueled by iron buildup and lipid peroxidation. Recent evidence points to the function of ferroptosis in the aetiology and development of cancer and other disorders. Consequently, harnessing iron death for disease treatment has diverted the interest of the researchers in the field of basic and clinical research. The ubiquitin-proteasome system (UPS) represents a primary protein degradation pathway in eukaryotes. It involves labelling proteins to be degraded by ubiquitin (Ub), followed by recognition and degradation by the proteasome. Dysfunction of the UPS can contribute to diverse pathological processes, emphasizing the importance of maintaining organismal homeostasis. The regulation of protein stability is a critical component of the intricate molecular mechanism underlying iron death.Moreover, the intricate involvement of the UPS in regulating iron death-related molecules and signaling pathways, providing valuable insights for targeted treatment strategies. Besides, it highlights the potential of ferroptosis as a promising target for cancer therapy, emphasizing the combination between ferroptosis and the UPS. The molecular mechanisms underlying ferroptosis, including key regulators such as glutathione peroxidase 4 (GPX4), cysteine/glutamate transporter (system XC-), and iron metabolism, are thoroughly examined, alongside the role of the UPS in modulating the abundance and activity of crucial proteins for ferroptotic cell death, such as GPX4, and nuclear factor erythroid 2-related factor 2 (NRF2). As a pivotal regulatory system for macromolecular homeostasis, the UPS substantially impacts ferroptosis by directly or indirectly modulating iron death-related molecules or associated signaling pathways. This review explores the involvement of the UPS in regulating iron death-related molecules and signaling pathways, providing valuable insights for the targeted treatment of diseases associated with ferroptosis.